Efeito antidepressivo e ansiolítico da riparina IV: envolvimento monoaminérgico, GABAérgico e neuroinflamatório. - Oliveira, Natália Ferreira de (2019)
Depression and anxiety are the most frequently occurring psychiatric disorders in society. Data from the World Health Organization show that depression is a major cause of disability in the world and is considered a public health problem, generating negative impacts on society and public systems. Overall, it is estimated that 4.4% of the world population suffers from depressive disorder and 3.6% from anxiety disorder. Theories on pathophysiology of depression are based on studies investigating psychosocial stress and related hormones, neurotransmitters, neurocircuits, neurotrophic factors, circadian rhythms, and the immune system. The aim of this study was to investigate the antidepressant and anxiolytic effects of acute treatment with Riparin IV in behavioral and neurochemical models in mice. Behavioral tests, such as forced swimming test and tail suspension test, were performed to investigate the antidepressant-like effects. Elevated plus maze and hole-board test were used to investigate anxiolytic-like effects. Open field and Rotarod, to evaluate spontaneous locomotor activity and motor coordination. In addition, the effects of riparin IV on neurochemicals tests such as monoamines and their metabolites, on cytokines (IL-6 and TNF-α) and oxidative stress in the hippocampus, prefrontal cortex and striatum were evaluated and computational prediction of the pharmacokinetics, affinity and mode of binding of Riparin IV to monoaminergic and GABAergic neurotransmission targets. This project was approved by the animal research ethics committee of the Federal University of Ceará. The results showed that riparin IV produced antidepressant-like and anxiolytic-like behavioral effects without modifying locomotor activity and motor coordination. The substance increased levels of monoamines and their metabolites in the hippocampus, prefrontal cortex and striatum of mice. In addition, the involvement of the noradrenergic (α2), dopaminergic (D1 and D2), serotonergic (5-HT2A / 2C and 5-HT3) and GABAergic systems in the mechanism of action of Riparin IV and a neuroprotective effect, mainly in the hippocampal region, observed with the decrease of malondialdehyde and nitrate / nitrite levels and the increase of reduced glutathione, catalase and superoxide desmutase enzyme activity. In silico, riparin IV has been shown to cross the blood-brain barrier, to have high gastrointestinal absorption and to have affinity to interact with the MAO-B and D2 receptors and serotonin and dopamine transporters, and may be a promising substance for the treatment of depression and associated depression anxiety.